Enterprise level responses to environmental institutional pressure: Focus on legitimization strategies. (1st January 2023) - Wang, Zhining; Doren, Chadee; Cai, Shaohan; Ren, Shuang
Abstract: This study investigates the nexus between macro level environmental institutional pressure and enterprise level green performance outcomes. We draw from legitimacy theory to develop a framework that explains how legitimization strategies help firms transform environmental institutional pressures into desired green performance outcomes. We test our model on a sample (n = 317) of technology-based manufacturing enterprises in China. Our results show that enterprise environmental commitment and green intellectual capital development play important roles in explaining the effects of environmental institutional pressure on green performance outcomes. The managerial implications of our findings and suggestions for future research in the context of mounting environmental institutional pressure on enterprises worldwide are fully discussed.